2017
DOI: 10.1093/jac/dkx138
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of vanA Enterococcus faecium in Denmark, 2005–15

Abstract: VRE increased in Denmark during 2005-15 due to the emergence of several vanA E. faecium clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 12 publications
0
30
0
2
Order By: Relevance
“…Such approaches provide results in high resolution for investigating closely related individuals, as in outbreaks mostly restricted to a local setting (e.g., one ward, one hospital, or one country) (52). In contrast, phylogenetic investigations on a “global” scale or long-term studies often lack a reference suitable for the entire set of strains to be analyzed (53). Although programs such as refRank will select for the best reference for a given data set, it is always a trade-off with respect to the genomic variety of the strain collection (39).…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches provide results in high resolution for investigating closely related individuals, as in outbreaks mostly restricted to a local setting (e.g., one ward, one hospital, or one country) (52). In contrast, phylogenetic investigations on a “global” scale or long-term studies often lack a reference suitable for the entire set of strains to be analyzed (53). Although programs such as refRank will select for the best reference for a given data set, it is always a trade-off with respect to the genomic variety of the strain collection (39).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the VRE isolates belonged to prominent German hospital-associated E. faecium lineages such as ST117, ST80, ST192, or ST203; almost all of them exhibited vanB-type vancomycin resistance, which recently emerged in German clinics [11]. Also as demonstrated by Hammerum et al, Danish VRE analyzed from 2005 to 2015 revealed genotypes such as ST80 (CT14), ST117 (CT24), and ST203 (CT859) [58]. Our study proved genotype ST117/CT469 as the predominant clone that was occasionally detected also in other countries such as Luxembourg and the Netherlands (www.cgMLST.org) and is known to be distributed across Germany [59].…”
Section: Molecular Analyses and Bioinformaticsmentioning
confidence: 91%
“…In Denmark, vanA Enterococcus faecium is most prevalent among clinical vancomycin-resistant Enterococcus (VRE) isolates ( 1 ).…”
Section: Announcementmentioning
confidence: 99%
“… E. faecium VRE1589 was the earliest vanA E. faecium isolate belonging to sequence type 203 and complex type 859 (ST203-CT859) identified among the VRE isolates submitted to Statens Serum Institut as part of the Danish national surveillance program. Comparison to the cgMLST.org database ( https://cgmlst.org/ncs ), previous Danish studies, and personal communications with neighboring countries with whole-genome sequencing (WGS) data available suggests that the novel complex type (CT859) emerged in October 2014 in Copenhagen and spread to the rest of Denmark, the south of Sweden, and the Faroe Islands during 2015 ( 1 ). In 2016, 64% of the clinical vanA E. faecium isolates detected in Denmark belonged to ST203 and CT859 ( 2 ).…”
Section: Announcementmentioning
confidence: 99%